Telaah studi kandungan probiotik pada fermentasi makanan khas di pulau Jawa - Novita Kusuma Wardani; R. Susanti; Talitha Widiatningrum (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
The food industry is one of the commodities that always grows and develops in line with the increasing needs and demands of the market. The growth in demand for fermented foods in the market is due in part to the increased interest in healthy food and the awareness of consumers' perceptions that fermentation is a naturally beneficial process. The ferementation process is inseparable from the role of probiotic microorganisms, bioactive compounds, and micronutrients produced through microbial action. This literature review study aims to analyze the role of probiotics in the fermentation of typical foods in Java, which have the potential to act as an immune regulatory system. The results of a literature study on various kinds of fermented specialties in Java and the manufacturing process show that the microbes that play a role in food fermentation consist of mold and bacteria. These microbes have the potential as an immune regulatory system.